Kepemimpinan Transformasional Kepala Sekolah Dalam Menanamkan Nilai-Nilai Islam di MA PPTQ Al-Ikhlas Sukoharjo - Syifa Amalia Khusna Kusumasari; Muhammad Wildan Shohib (Kamaya: Jurnal Ilmu Agama, 2026)
Islamic education plays a crucial role in character building, where success is heavily influenced by the principal's leadership quality. While transformational leadership is widely discussed, specific studies focusing on its strategy for internalizing Islamic values within the Madrasah Aliyah (MA) level in a Tahfiz boarding school context remain scarce. This study aims to analyze the principal's transformational leadership roles and strategies in instilling Islamic values at MA PPTQ Al-Ikhlas Sukoharjo. Employing a qualitative descriptive method with a phenomenological approach, data were gathered through interviews, observations, and documentation, then analyzed using the Miles and Huberman interactive model. The findings reveal that the principal serves strategic roles as a spiritual leader, HR developer, environment builder, and curriculum integrator. Key strategies include teacher quality enhancement, deliberation-based communication, and Islamic culture habituation. The novelty of this research lies in the emphasis on the teacher-environment-curriculum strategic pattern as an effective value internalization model. Practically, this study provides a reference for Islamic education managers in developing adaptive and sustainable leadership.